ANALISIS JENIS PLASTIK DAN MINYAK PLASTIK PYROLYSIS-RON 90 TERHADAP DAYA DAN EMISI MOTOR 150 CC: ANALYSIS OF TYPES PLASTIC AND PLASTIC OIL PYROLYSIS-RON 90 ON 150 CC MOTOR POWER AND EMISSIONS - Fath Agung Brigytta, Fath Agung Brigytta (Jurnal Teknik Mesin, 2022)
Energy is one of the needs in everyday life where the main need for energy still depends on fossil fuels, oil and gas. Fuel is one of the second most important needs after human needs for food, clothing and shelter. The method used is experimental with the aim of research to find the best mixture of pertalite and fuel produced by pyrolysis of plastic waste. The results of this test show that for the highest power and lowest emissions using pyrolysis fuel type PP plastic waste in a mixture of 10% plastic oil and 90% RON 90 produces 9.49 hp and CO emissions of 0.48% and HC 68 ppm